2015
DOI: 10.1038/ncomms9091
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel animal societies can emerge from cultural transmission

Abstract: Multilevel societies, containing hierarchically nested social levels, are remarkable social structures whose origins are unclear. The social relationships of sperm whales are organized in a multilevel society with an upper level composed of clans of individuals communicating using similar patterns of clicks (codas). Using agent-based models informed by an 18-year empirical study, we show that clans are unlikely products of stochastic processes (genetic or cultural drift) but likely originate from cultural tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 69 publications
4
99
0
Order By: Relevance
“…Long-term studies of nonhuman animal species in their natural habitats have demonstrated that many species respond to, and learn from, social information (4)(5)(6)(7)(8)(9). Nonhuman animals also transmit group-specific behavior through what could be considered rudimentary forms of cultural transmission (10)(11)(12)(13)(14). However, cultural transmission in humans differs markedly from that in nonhuman animals in both its extent and structural complexity (15,16).…”
mentioning
confidence: 99%
“…Long-term studies of nonhuman animal species in their natural habitats have demonstrated that many species respond to, and learn from, social information (4)(5)(6)(7)(8)(9). Nonhuman animals also transmit group-specific behavior through what could be considered rudimentary forms of cultural transmission (10)(11)(12)(13)(14). However, cultural transmission in humans differs markedly from that in nonhuman animals in both its extent and structural complexity (15,16).…”
mentioning
confidence: 99%
“…Females, and sometimes males, typically spend their lives with their mothers and other maternal relatives. Not only does this association increase the potential learning period and number of models, but the behavior within these matrilineal social units may become very stereotyped, through processes such as conformism and symbolic marking (82). These factors increase the range of ways culture can affect genes, especially the matrilineally transmitted mitochondrial genes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that, for other social cetaceans, variability in the vocal repertoire can be both socially driven [e.g., killer whales (Yurk et al, 2002;Riesch et al, 2006;Deecke et al, 2010;Filatova et al, 2012;Crance et al, 2014;Musser et al, 2014) and sperm whales (e.g., Rendell et al, 2012;Cantor et al, 2015)] and behaviorally driven [e.g., killer whales (Filatova et al, 2013;Holt et al, 2013)]. Shortfinned pilot whales are a highly social cetacean, known to form stable social groups for a decade or more (HeimlichBoran and Hall, 1993;Mahaffy et al, 2015).…”
Section: Future Workmentioning
confidence: 99%